Acceptability of a Comprehensive Sex Education Self-Study Website for Teaching Reproductive Health: A Pilot Study Among College Students and Obstetrics and Gynecology Resident Physicians. Issue 1 (8th January 2021) - Yoost, Jennie; Ruley, Morgan; Durfee, Levi
Abstract: Introduction: There is a growing interest among adolescents to obtain sexual health information online, which could be helpful in rural areas where adolescents face unique obstacles to contraception access, and medically accurate sex education is not mandated. Aim: This study piloted a comprehensive sex education self-study website among undergraduate students and resident physicians to assess the accuracy and feasibility for future use in younger adolescents. Methods: A sex education website developed by a board-certified obstetrician-gynecologist (OBGYN) was piloted among a group of OBGYN resident physicians and undergraduates from West Virginia. Groups were chosen to assess the accuracy of information and acceptability for use in younger adolescents. The 30-minute curriculum was a series of short videos (2–4 minutes each) covering anatomy, physiology, sexuality, gender identity, relationship health, contraception, and sexually transmitted infection prevention. Data were obtained on subjects' past experience and perception of sex education. Subjects also evaluated the website for usefulness and accuracy. Outcomes: Main outcomes included a Likert scale assessment of each curriculum session's usefulness, accuracy, and how easy it was to follow. Results: 24 subjects (14 undergraduates and 10 physicians) participated during September and October of 2019. All except for 1 subject had sex education taught in school; 11 (45.8%) reported it to be "low quality"; 23 (95.8%) reported being taught in a classroom. Individual website video sessions were reported to be highly accurate, very easy to follow, and very useful. All subjects (100%) felt that high school adolescents would be interested in the self-study website. Conclusions: A self-study website was successfully tested and found to be a well-accepted way to teach sex education among this pilot group. Future work involves testing this tool among younger adolescent subjects.